Fecal microbiota of free-range pigs (Sus scrofa domesticus) scavenging on a municipal dumpsite is a potential reservoir of pathogens - Mwaikono, K.S.; Maina, Solomon; Gwakisa, P.S. (Science and Education Publishing Co., Ltd., 2018)
Free-range food animals scavenging in urban and peri-urban dumpsites are exposed to diverse microbes of public health importance, yet little is known of their fecal microbiota and public health implication. We characterized the fecal microbiota of pigs scavenging at a municipal dumpsite (FecD, n =19) by MiSeq sequencing for 16S rRNA and compared with conventionally indoor reared pigs (FecI, n = 21). A total of 4,364,507 sequences with an average of 114,852 reads per sample passed quality control. The predicted mean of species per sample was 5,979. There was no difference in alpha diversity between free-range and indoor pigs (InvSimpson 23.68 vs 38.06, p = 0.1091 and Shannon 5.60 vs 6.41, p = 0.053). The community membership and population structure were significantly different (Yue and Clayton p = 0.001 and Jaccard p = 0.014). Bacterial genera significantly associated with free-range pigs were Bifidobacterium, Enterococcus, Turicibacter and Cellulosilyticus; while in indoor pigs were Prevotella, Fibrobacter, Megasphaera, Allisonella, fibrobacteres and Phascolarctobacterium. Metagenome prediction revealed that Tetracycline biosynthesis, Staphylococcus infection, sporulation and Vibrio cholerae pathogenic pathways are significantly (p Proteobacteria rich in mobile elements and pathogenic potential. Free-range pigs scavenging in urban and peri-urban areas are potential reservoirs of pathogens of public health importance. These findings suggest indoor management of animals in urban and peri-urban areas to mitigate possible health risks from free-range animals which might get into food chain. Further study of the gut microflora of free-range pigs at dumpsites and their clinical significance to humans and other animals is warranted.